An introduction to criminal and civil law [ (Video Education Australasia, 2007)
What are the differences between criminal and civil law, and how do we decide whether a situation is part of criminal law or civil law or both? This program begins with a brief description of legal and non-legal rules, and then examines what constitutes a criminal act, the difference between a summary and indictable offence and the principles of criminal liability. The program examines civil law and its purpose in society while looking also at the two major branches of civil law, Law of Torts and Law of Contract." -- container. Law, and how do we decided whether a situation is part of criminal law or civil law or both?